PROMOTING THE PRODUCTS OF SPEED ELECTRONICS USING A COMMERCIAL WEBSITE - Martha Stefani; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
Speed Electronics is a home industry which producing electronic spare-parts for electronic goods. Since this company is still developing, it has to deal with several promotion problems. To solve this problem, Speed Electronics really needs to have a media which can promote its products and attract prospective customers. Thus, a commercial website will be suitable for Speed Electronics. It will consist of “Home”, “About Us”, “Our Products”, “Our Service”, “Our Distributors/Stores” and “How to Contact Us” parts. I believe only by seeing the pictures and the descriptions inside the website, the customers will be updated with the newest information about the spare-parts that Speed Electronics sell. Moreover, when they want to order the spare-parts, they can directly look at this website to avoid miscommunication. Besides, Speed Electronics will expectedly be able to widen its market or even get a chance to export its products to other countries